Higher serum Metrnl levels are associated with increased vascular calcification in hemodialysis patients - Conghui Liu; Wenwen Ren; Aihua Zhang (Renal Failure)
Background Meteorin-like (Metrnl) is a newly identified secreted protein that plays important roles in metabolic and inflammation-related diseases. Our study aimed to evaluate serum Metrnl levels and establish their relationship with vascular calcification (VC) in hemodialysis (HD) patients.Methods In total, 313 HD patients and 41 healthy individuals, as controls, were included. Serum levels of Metrnl and other clinical and laboratory parameters were compared. VC was evaluated based on the abdominal aortic calcification (AAC) scores. HD patients were divided into a high-AAC score group (AAC score ≥ 4) and a low-AAC score group (AAC score < 4).Results HD patients had higher serum Metrnl levels than the controls (0.52 ± 0.26 ng/ml vs. 0.24 ± 0.11 ng/ml, p < 0.001). Serum Metrnl concentrations were significantly higher in HD patients in the high-AAC score group than in those in the low-AAC score group (0.55 ± 0.27 vs. 0.49 ± 0.24 ng/ml, p = 0.041). Multivariate logistic regression revealed that serum Metrnl, age, diabetes mellitus, serum total carbon dioxide (tCO2) and serum intact parathyroid hormone (iPTH) were significant independent determinants of high AAC scores.Conclusion The results herein provide the first clinical evidence of the association between serum Metrnl and VC in HD patients. Higher Metrnl levels, older age, diabetes mellitus, and higher serum tCO2 and iPTH levels are independent determining factors for high AAC scores in HD patients.